Trabalho docente, racionalidade técnica e adoecimento: um olhar à luz da teoria crítica da sociedade - Santos, Jussimária Almeida dos (2023)
Taking as theoretical reference the perspective of the Frankfurt School Critical Theory of Society, especially from the analysis of Theodor W. Adorno, Max Horkheimer and Herbert Marcuse, this research proposed to reflect on the relationship of teacher illness in interface with technical rationality in the context of the administered world and how this resonates in the process of division, precariousness, expropriation and alienation in labor relations. The goal was to examine the implications of work on teachers' lives, especially in terms of physical and mental health in the socio-political and cultural spheres. Some analyses were formulated based on Karl Marx's work as a category, which served as a guide to delineate the investigation about the process of getting sick in relation to work, given the conflicts inherent to a process of technical and technological transformations in capitalist society. In the context of this contradiction, teachers are faced with a crisis of teachers' uneasiness, suffering and, consequently, in getting sick, allowing us to resort to Georges Canguilhem and Sigmund Freud to deal with the aspects between health and disease, as well as the (im)possibilities of the "cure" in which the body is the main source of suffering in the relationship with the infidelities of the environment. This is justified in work situations as an educational action, because there is a "dynamic polarity of life". Among the main discussions, the cultural industry stood out in the process of (pseudo)formation, which involves the teacher in a stage of conformism in front of the media, uncritically influencing his/her teaching performance. Finally, another dimension revealed in this study in interlocution with the Frankfurtian critical theory, refers to the analytical contribution of the research on mental health and illness at work, conducted by Christophe Dejours and Edith Seligmann-Silva, in which they reaffirm the phenomenon of illness as an impediment to the quality of life in the context of the organization and work relations. From this perspective, these authors signaled the ways of dealing with illness at work, indicating resistance by intervening in the work space and in the organization, thus avoiding work structures that make people ill, this perspective does not ignore the contradictions referring to social limits and normative issues referring to biological aspects.